TRPA1 modulates noxious odor responses in Lygus hesperus. (April 2020) - Hull, J. Joe; Yang, Yu-Wen; Miyasaki, Katelyn; Brent, Colin S.
Graphical abstract: Highlights: L. hesperus increase movement velocity and duration if exposed to noxious odors. The L. hesperus transcriptome contains sequences for Orco and TRPA1. RNAi knockdown of TRPA1, but not Orco, reduces the noxious odor response. Abstract: Lygus hesperus is a key pest of many economically important crops across western North America. Central to many aspects of the lives of these insects is chemical signalling, with identified roles in host plant selection, aggregation and passive mate guarding. The development of novel monitoring and control approaches for this insect will rely on a sound understanding of how these cues are perceived and processed, and their impact on behavior. Towards this end, we investigated allyl isothiocyanate, cinnamaldehyde and citronellal, compounds that are noxious repellents to other insects. We found that L. hesperus avoided areas containing the three compounds and that exposure induced increases in movement velocity and duration in both nymphs and adults. This suggests these compounds may work as repellents. To better understand the underlying physiology of this response, RNA interference by dsRNA injection was used to inhibit the expression of two chemosensory-associated proteins, the odorant receptor co-receptor (Orco) and the transient receptor potential A (TRPA1) channel. While knockdown of Orco did not change the reaction of adult females to citronellal, TRPA1 silencing effectively eliminated the induced increase to movement, suggesting a chemoperceptory role in citronellal detection.